EDUKASI DAN PEMBERIAN TERAPI LATIHAN PADA PASIEN PPOK UNTUK MENGURANGI SESAK NAPAS DI RSUD DUNGUS - Natasya Anjani; Kristiyono Putro; Nungki Marlian Yuliadarwati (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Dungus Lung Hospital is a lung hospital in Madiun Regency, East Java. The majority of patients at the pulmonary hospital are elderly and suffer from respiratory problems. At an advanced age, the cardiorespiratory system will experience a decrease in endurance. Lung function will decrease due to reduced elasticity of the lung tissue and chest wall, making it difficult to breathe. Some lung diseases that are often suffered are tuberculosis, pneumonia, lung cancer, chronic obstructive pulmonary disease (COPD), bronchial asthma, and bronchitis. Counseling activities were carried out with the aim of providing education and exercise therapy to 20 patients related to conditions when shortness of breath. The counseling presentation includes definitions, clinical descriptions of signs and symptoms, recommended positions when shortness of breath, as well as providing home program-based exercise therapy that can be done independently. The counseling media used was in the form of a leaflet equipped with a description of the exercise pictures.